Rock-a-bye baby - Collins, Heather (Toronto ; Tonawanda, NY : Kids Can Press, 2000)
An illustrated version of the traditional nursery rhyme about a baby in the treetops.
Cover title.
On board pages.
1.4
K-3
K-3
Keywords: Nursery rhymes; Children's poetry; Nursery rhymes; Poetry; Nursery rhymes; Children's poetry